Luffa (Luffa cylindrica) as a material for shoes or slipper midsole / Adibah Ambo Asah, Farzana Huda Yanto and Nursazatulniya Sato - Asah, Adibah Ambo; Yanto, Farzana Huda; Sato, Nursazatulniya (Faculty of Plantation and Agrotechnology, 2023)
Luffa (Luffa cylindrica) is from member of cucurbitaceous family. It is a vegetable that can be used in many situations. It is used for food made into vegetables and can also be used as a body brush when bathing and used as a dishwashing brush at home. Our innovation focuses on luffa as a material that can be used as a midsole in shoes or slippers. The reinforced composite luffa sponge was used as a midsole for shoes or slippers to dampen vibration actively and critically. During running exercise, the damped vibration prevents knee and ankle injuries. The dried mat and chopped luffa sponge fibers were treated with a molar solution of sodium hydroxide to improve mechanical interlock and reaction sites. The matrix is then used as a binder and reinforcement to improve the Young's modulus and loss factor. There were tests for dynamic impact vibration, compression, low cyclic fatigue (LCF), and high cyclic fatigue (HCF). As a result, using past studies from (Zhang, Z., & Zuo, J. 2022) and (AKANO, T. T., & SUBERU, I. 2019). said that the reinforced composite luffa sponge is a fantastic solution for running shoe midsoles since it reduces running-related vibrations. The materials of luffa which is biodegradable is less environmental impact and it is also good for short-term energy storage.